Effect of Aerobic Exercise on Dynamic Balance in Menopausal Women: A Systematic Review - Mansyur, Khalisya Salsabila Savitri; Djawas, Faizah Abdullah (Poltekkes Kemenkes Surakarta, 2026)
Background: Menopause is a natural biological phase in women characterized by a decline in estrogen levels, which contributes to musculoskeletal deterioration and impaired balance function. Reduced dynamic balance in menopausal women increases the risk of falls and may affect functional independence. Aerobic exercise has the potential to serve as a non-pharmacological intervention to improve postural stability and neuromuscular function. This study aimed to systematically review the effects of aerobic exercise on improving dynamic balance in menopausal women. Methods: This study employed a systematic literature review based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Literature searches were conducted in Google Scholar, Semantic Scholar, and PubMed databases for articles published between 2015 and 2025. The inclusion criteria included experimental studies involving menopausal or postmenopausal women receiving aerobic exercise interventions with outcomes related to balance, mobility, or fall risk. Studies were excluded if they were reviews, conference papers, non-experimental designs, did not involve aerobic exercise, or had incomplete data. Results: Four studies met the inclusion criteria. The findings indicated that aerobic exercise, either as a standalone intervention or combined with strength and balance training, was associated with improvements in dynamic balance, functional mobility, and a reduction in fall risk among menopausal and postmenopausal women. Conclusion: Aerobic exercise is effective in improving dynamic balance in menopausal women and may be recommended as a non-pharmacological physiotherapy intervention to prevent balance decline and reduce fall risk.